Um Maranhão ilustrado?: história e natureza na correspondência entre D. Rodrigo de Sousa Coutinho e D. Diogo de Sousa (1798-1801) - Costa Junior, Flávio Pereira (2016)
Between the eighteenth and nineteenth centuries, intensify research on the nature of Portuguese America. This process had one of the main characters a Minister, D. Rodrigo de Sousa Coutinho (1796-1801). At that time it was founded the typography Arco do Cego, institution responsible for producing books that should be sent to the Conquests. The captaincies of Maranhão and Piauí were inserted in this context, but also had its peculiarities. The aim of this work is to discuss the circulation of knowledge about nature in Maranhão and Piauí, and understand what their role in the projects of Portuguese bureaucracy in that part of the world.